ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION TO INCREASE INTEREST IN REPURCHASE AT BLIRIK COFFEE RESTAURANT - Muryanto Agus Nuswantoro; Teti Susilowati; AsahWiari Sidiq (SEAN Institute, 2023)
The purpose of this study was to analyze the effect of service quality on consumer satisfaction in order to increase repeat purchase intention at Kopi Blirik Restaurant located in Mijen District, Semarang City. The population in this study were visitors to the Kopi Blirik Restaurant who were over 17 years old. Samples taken as many as 75 people. The sample data collection technique in this study was carried out using a purposive sampling technique. The data processing method uses SPSS. The results of the regression analysis show the effect of service quality, including tangible (X1) has a positive effect of 0.478, reliability (X2) has a positive effect of 0.114, responsiveness (X3) has a positive effect of 0.125. While the coefficient of determination on the independent variables, namely tangible, reliability, and responsiveness, is able to explain the variations that occur in the dependent variable, namely customer satisfaction (Y) of 36.9%. From the results of the t test the tangible variables (X1), reliability (X2), and responsiveness (X3) have a positive and significant effect on the consumer satisfaction variable (Y1), while consumer satisfaction also has a positive and significant effect on repurchase intention (Y2).